2019
DOI: 10.3390/ijms20215395
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Pipeline for Validation of Disease-Modifying Effects of Systems Biology-Derived Network Treatments for Traumatic Brain Injury—Lessons Learned

Abstract: We developed a pipeline for the discovery of transcriptomics-derived disease-modifying therapies and used it to validate treatments in vitro and in vivo that could be repurposed for TBI treatment. Desmethylclomipramine, ionomycin, sirolimus and trimipramine, identified by in silico LINCS analysis as candidate treatments modulating the TBI-induced transcriptomics networks, were tested in neuron-BV2 microglial co-cultures, using tumour necrosis factor α as a monitoring biomarker for neuroinflammation, nitrite fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…Even with the strong in vitro efficacy of a drug, the in vivo validation process may not be sensitive enough to demonstrate favorable in vivo effects [ 72 ]. As our in vitro study indicated, not only monotherapy with SFN but also monotherapy with NAC had anti-inflammatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the strong in vitro efficacy of a drug, the in vivo validation process may not be sensitive enough to demonstrate favorable in vivo effects [ 72 ]. As our in vitro study indicated, not only monotherapy with SFN but also monotherapy with NAC had anti-inflammatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebral cortex of each of the E18 embryos was dissected and the neuronal cells were plated as described earlier [ 41 , 42 ]. Briefly, the cortex was dissected under a stereomicroscope in Dulbecco’s modified Eagles medium (DMEM; #BE12-614F, Lonza, Basel, Switzerland), supplemented with 10% fetal bovine serum (#10270-106, Thermo Fisher Scientific, Waltham, MA, USA) and 2 mM l-glutamine (#BE17-605E, Lonza).…”
Section: Methodsmentioning
confidence: 99%
“…developed a unique pipeline for TBI treatment discovery using transcriptomics data. [ 43 ] The outcomes of their approach identified several potential drug candidates that could modulate the inflammatory response post-TBI, offering a new avenue for TBI treatment. [ 43 ]…”
Section: Targeting Inflammation and Oxidative Stressmentioning
confidence: 99%